Do mechanical advantages exist in relining fiber posts with composite prior to its cementation? - Dal Piva, Amanda Maria de Oliveira [UNESP]; Tribst, João Paulo Mendes [UNESP]; Borges, Alexandre Luiz Souto; Bottino, Marco Antonio; e Souza, Rodrigo Othávio de Assunção (My University, 2018)
Purpose: To evaluate two different techniques for glass fiber-reinforced resin post (FRC) insertion by assessing the stress distribution under polymerization shrinkage or masticatory loading and measuring the pull-out bond strength to dentin. Materials and Methods: A model of an endodontically treated maxillary central incisor was used for three-dimensional simulation with two conditions: conventionally cemented (FRC) and relined (RFRC). The volumetric solids were exported to analysis software (ANSYS 17.2, ANSYS) in STEP (Standard for the Exchange of Product Data) format. All contacts were considered perfectly bonded between the geometries. Numerical models received a load of 100 N (45 degrees) on the lingual surface. The composite cement polymerization shrinkage was simulated by thermal analogy to obtain Von Mises, maximum principal stress, and shear stress. For in vitro evaluation, a pull-out bond strength test (n = 20/N = 40) was performed (50 Kgf, 1 mm/min) after mechanical cycling (in water at 37°C, 84 N, 2 bar, 45 degrees, 106 cycles, 4 Hz), and failure analysis was subsequently performed. The results were analyzed using one-way ANOVA and Tukey's test (α < 0.05). Results: The FRC group showed more stress concentration in the cement layer. The RFRC group [(32 ± 13); (288 ± 129)] presented better performance than the FRC group [(6 ± 7); (152 ± 87)] for stress distribution and bond strength (p < 0.05). Adhesive and mixed failures occurred in both groups. Conclusion: Relined fiberglass posts reduced the stress generated by polymerization shrinkage and showed greater bond strength to dentin.
Keywords: Endodontic fiber post; Finite element analysis; Shear strength; Shrinkage stress